Characterization of cotton cultivation: spatio-temporal considerations for Mato Grosso State - José, Jefferson Vieira; Freitas, Kelly Cristina da Silva; Costa, Jéfferson de Oliveira; Quiloango-Chimarro, Carlos Alberto; Bonfim-Silva, Edna Maria; da Silva, Tonny Jose de Araújo (Revista Brasileira de Engenharia de Biossistemas, 2022)
The State of Mato Grosso produces approximately 45% of cotton in Brazil, which makes it necessary to characterize the crop in this State. The objective was to analyze cotton production in the State of Mato Grosso through official data from the IBGE’s Systematic Survey of Agricultural Production (LSPA), both for micro-regions and meso-regions. Temporal graphs and maps were constructed for planted area, quantity produced and yield. Temperature and precipitation were analyzed for the crop cycle period. Northern Mato Grosso has the largest area and quantity of seed cotton production. It is also the mesoregion with the highest growth between 2005 and 2016. However, fluctuations in planted area were reported due to supply and demand issues. The Parecis micro-region is highlighted as the one with the highest production, area and productivity. In addition, climatic factors suggest that most micro-regions are ideal for cotton production. In conclusion, production and productivity in Mato Grosso State can continue to increase with a stable market and the introduction of technology.